Temperature control of CSTR using PID Controller (International Journal of Engineering and Computer Science, 2015)
Continuous stirred tank reactor system is a typical chemical reactor system with complex nonlinear dynamics characteristics. The purpose of this paper is to control the temperature of CSTR using PID controller and with the help of ZIEGLER NICHOLS method and we are done tuning of PID controller. The whole process of model design of and result, simulation are done in MATLAB SIMULINK software.